Studies on Severity, Comparative Preponderance, Cultural and Morphological Variability of Alternaria Species Causing Alternaria Blight of Yellow Sarson (Brassica campestris L. var. Yellow Sarson Prain) - Kumar, Sunil; Singh, R. B.; Shakywar, R. C. (International Journal of Bio-resource and Stress Management, 2023)
A field experiment was conducted during rabi of 2006-07 and 2007-08 to study the severity, comparative preponderance, cultural and morphological variability of Alternaria spp. causing Alternaria blight of yellow sarson (Brassica campestris L. var. yellow sarson Prain) in field as well as in laboratory of Plant Pathology (NDUAT, Kumarganj, Faizabad). Alternaria blight initiated earliest on second week of December during both the years in the cultivars NDYS 2 and NDYS 2018 attaining highest PDI of 69.90 and 69.95% during first year and 75.60 and 76.65% during second year, respectively in 20 October sown crop. Among the entries average maximum colony diameter of A. brassicae was noted in NDYS 2018 (35.67 mm) with range of 34-38 mm followed by NDYS 123 (34.67 mm) with range of 33-37 mm and NDYS 2 (34.33 mm) with range of 32-36 mm. Both the species i.e. A. brassicae and Alternaria brassicicola were isolated from infected leaf, stem and pods. Average maximum conidial width of A. brassicae and A. brassicicola was noted in case of leaves (20.57 µ and 12.60 µ) followed by pods (19.11 µ and 11.59 µ) and stem (14.74 µ and 10.93 µ), respectively. Frequency of occurrence of Alternaria brassicae was noted higher in case of affected leaves and pods, while Alternaria brassicicola was found higher in affected stem. Alternaria brassicae and Alternaria brassicicola isolates obtained from leaves, stem and pods showed variability in colony diameter, shape and size of conidiophores, conidia and septation in conidia.